#Aboriginallivesmatter: Mapping Black Lives Matter discourse in Australia. (August 2022) - Dejmanee, Tisha; Millar, Jeffrey; Lorenz, Marni; Weber, Kirsten; Zaher, Zulfia
This paper explores the hashtag #AboriginalLivesMatter on Instagram which was widely used in Australia as part of a global Black Lives Matter (BLM) response in 2020. We map the participants and themes of #AboriginalLivesMatter through the quantitative coding and qualitative thematic analysis of 603 Instagram posts published with this hashtag in June 2020. We find that this conversation is largely driven by celebrities and non-Indigenous participants and framed by themes including expressing the problem as first-person experience, offering solutions, reporting, performing empty statements, and expressing US-centrism. Drawing on critiques of connective action and our analysis of the Instagram platform, we suggest that these findings are indicative of the tensions negotiated between incorporating allies on platforms that prioritise sharing first-person experiences; balancing the communicative capacities of Instagram with its inherently commercialised digital cultures; and, drawing on the spreadability of global digital movements while maintaining cultural specificity for local activists.